Navigating New Terrain: Exploring Orientation Programs For New Academic Staff and Their Experience - Hussin, Anealka Aziz; Paridaluddin, Noorfarida Filzah Mohd Sobri; Hashim, Haida Umiera; Ismail, Nur Asyrani Che; Sukri, Hanna Insyirah Mohd (International Journal of Scientific Research and Management (IJSRM), 2024)
Commencing a new job can instigate anxiety, especially for those without prior work experience. The excitement of a fresh employment endeavour may coincide with feelings of discomfort, stemming from unfamiliar expectations. A comprehensive overview and understanding on orientation programs for new staff can play a crucial role in facilitating their adaptation, fostering departmental understanding, fostering colleague connections, and grasping job essentials. This research seeks to assess orientation activities carried out for new academic staff joining the faculty by the management while investigating the orientation program experience of recently onboarded staff members with less than six years of experience in one of the language academies in a public university in the Klang Valley. An interview and survey were conducted and revealed notable areas of concern including employee benefits, performance expectations, departmental and faculty structures, policies and procedures and training development. The findings delineated key areas of concern as a foundational framework to be concentrated by the management during future faculty staff recruitment.  This study also highlights the need to develop a tailored orientation kit for new onboarding staff to the faculty.